The mTOR Inhibitor Temsirolimus Added to Rituximab Combined With Dexamethasone, Cytarabine, and Cisplatinum (R-DHAP) for the Treatment of Patients With Relapsed or Refractory DLBCL – Results From the Phase-II STORM Trial. Issue 10 (23rd October 2021) - Witzens-Harig, Mathias; Viardot, Andreas; Keller, Ulrich; Wosniok, Julia; Deuster, Oliver; Klemmer, Jennifer; Geueke, Anne-Marie; Meißner, Julia; Ho, Anthony D.; Atta, Johannes; Marks, Reinhard; La Rosée, Paul; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : There is a high need for novel treatment options in relapsed and refractory diffuse large B-cell lymphoma. Single agent mammalian target of rapamycin (mTOR) inhibitor treatment has shown promising efficacy in this entity. Here, we report on the results of the mTOR-inhibitor temsirolimus combined to standard rituximab-DHAP salvage regimen in a prospective, multicenter, phase II, open-label study. The STORM regimen consisted of rituximab 375 mg/m 2 (day 2) and DHAP (dexamethasone 40 mg day 3-6, cisplatinum 100 mg/m 2 day 3, cytarabine 2 × 2 g/m 2 day 4) with temsirolimus added on day 1 and 8 of a 21-day cycle, with 2 to 4 cycles planned. In part I, dose levels of 25, 50, 75, and 100 mg for temsirolimus were predefined. Based on the observed toxicity profile, a temsirolimus dose of 25 mg was defined as recommended dose for the part II extension cohort of the trial. The intention-to-treat cohort comprised 53 patients. Median age was 63 years and median number of prior regimen was 1. All but 1 patient had prior rituximab exposure. Temsirolimus dose was 50 mg on day 1 and 8 in 6 patients from the part I of the trial and 25 mg in the remaining 47 patients. In general, treatment was well tolerated with leucopenia and thrombocytopenia as most frequent severe adverse events. The overall response rate after the last cycle of temsirolimus R-DHAP was 66% with 24% complete responses. The ability to mobilize stem cells was not impaired by the treatment regimen. Twenty-eight patients received consolidation treatment with high-dose therapy (HDT) and stem cell transplantation. Median duration of response was not reached. The total 2-year progression-free survival (PFS) and overall survival (OS) were 53% and 59%. Patients who were consolidated with HDT achieved a 2-year PFS and a 2-year OS of 77.8% and 82.1%, respectively. We conclude that temsirolimus can be safely added to rituximab and DHAP with promising activity.